NETWORK CONSTRAINED UNIT COMMITMENT MENGGUNAKAN METODE ALGORITMA GENETIKA DENGAN PENDEKATAN METODE PRIORITY LIST MEMPERTIMBANGKAN KEKANGAN KEANDALAN - , Arief Budi Mulyawan ([Yogyakarta] : Universitas Gadjah Mada, 2014)
With the increasing of complexity in electrical power systemWith the increasing of complexity in electrical power system With the increasing of complexity in electrical power system With the increasing of complexity in electrical power system With the increasing of complexity in electrical power system With the increasing of complexity in electrical power systemWith the increasing of complexity in electrical power systemWith the increasing of complexity in electrical power system With the increasing of complexity in electrical power system With the increasing of complexity in electrical power systemWith the increasing of complexity in electrical power systemWith the increasing of complexity in electrical power system With the increasing of complexity in electrical power systemWith the increasing of complexity in electrical power system With the increasing of complexity in electrical power systemWith the increasing of complexity in electrical power systemWith the increasing of complexity in electrical power system With the increasing of complexity in electrical power systemWith the increasing of complexity in electrical power system With the increasing of complexity in electrical power systemWith the increasing of complexity in electrical power system With the increasing of complexity in electrical power systemWith the increasing of complexity in electrical power systemWith the increasing of complexity in electrical power system With the increasing of complexity in electrical power system With the increasing of complexity in electrical power systemWith the increasing of complexity in electrical power systemWith the increasing of complexity in electrical power system s, starting starting starting starting from from generation to the distribution, it provides a separate issue electrical generation to the distribution, it provides a separate issue electrical generation to the distribution, it provides a separate issue electrical generation to the distribution, it provides a separate issue electrical generation to the distribution, it provides a separate issue electrical generation to the distribution, it provides a separate issue electrical generation to the distribution, it provides a separate issue electrical generation to the distribution, it provides a separate issue electrical generation to the distribution, it provides a separate issue electrical generation to the distribution, it provides a separate issue electrical generation to the distribution, it provides a separate issue electrical generation to the distribution, it provides a separate issue electrical generation to the distribution, it provides a separate issue electrical generation to the distribution, it provides a separate issue electrical generation to the distribution, it provides a separate issue electrical generation to the distribution, it provides a separate issue electrical generation to the distribution, it provides a separate issue electrical generation to the distribution, it provides a separate issue electrical generation to the distribution, it provides a separate issue electrical generation to the distribution, it provides a separate issue electrical generation to the distribution, it provides a separate issue electrical generation to the distribution, it provides a separate issue electrical generation to the distribution, it provides a separate issue electrical generation to the distribution, it provides a separate issue electrical generation to the distribution, it provides a separate issue electrical generation to the distribution, it provides a separate issue electrical generation to the distribution, it provides a separate issue electrical generation to the distribution, it provides a separate issue electrical generation to the distribution, it provides a separate issue electrical generation to the distribution, it provides a separate issue electrical generation to the distribution, it provides a separate issue electrical generation to the distribution, it provides a separate issue electrical generation to the distribution, it provides a separate issue electrical world. world. Especially i Especially iEspecially i Especially iEspecially iEspecially in generation system n generation system n generation system n generation system n generation system n generation system n generation systemn generation systemn generation system , one ne of the problems of the problems of the problems of the problems of the problems of the problems is the high of is the high of is the high of is the high of is the high of is the high of generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This generation cost due to the increasing of fuel used and capacity. This problem problem is one of th is one of th is one of this one of th is one of this one of th e optimization problems which exist in power systeme optimization problems which exist in power systeme optimization problems which exist in power system e optimization problems which exist in power system e optimization problems which exist in power systeme optimization problems which exist in power systeme optimization problems which exist in power systeme optimization problems which exist in power system e optimization problems which exist in power system e optimization problems which exist in power system e optimization problems which exist in power systeme optimization problems which exist in power system e optimization problems which exist in power systeme optimization problems which exist in power system e optimization problems which exist in power systeme optimization problems which exist in power system e optimization problems which exist in power system e optimization problems which exist in power system e optimization problems which exist in power systeme optimization problems which exist in power systeme optimization problems which exist in power system . To minimize the generation operational cost minimize the generation operational cost minimize the generation operational costminimize the generation operational costminimize the generation operational costminimize the generation operational costminimize the generation operational cost minimize the generation operational cost minimize the generation operational costminimize the generation operational costminimize the generation operational cost minimize the generation operational cost minimize the generation operational cost minimize the generation operational cost minimize the generation operational cost minimize the generation operational cost minimize the generation operational cost minimize the generation operational cost minimize the generation operational costminimize the generation operational cost , generation scheduling or usually called generation scheduling or usually called generation scheduling or usually called generation scheduling or usually called generation scheduling or usually called generation scheduling or usually called generation scheduling or usually called generation scheduling or usually called generation scheduling or usually called generation scheduling or usually called generation scheduling or usually called generation scheduling or usually called generation scheduling or usually called generation scheduling or usually called generation scheduling or usually called generation scheduling or usually called generation scheduling or usually called generation scheduling or usually called generation scheduling or usually called generation scheduling or usually called generation scheduling or usually called unit commitment (UC) unit commitment (UC) unit commitment (UC) unit commitment (UC) unit commitment (UC) unit commitment (UC) must be optimized firstmust be optimized first must be optimized first must be optimized firstmust be optimized firstmust be optimized first must be optimized first . In this In this In this In this In this research, UC is modeled research, UC is modeled research, UC is modeled research, UC is modeled research, UC is modeled research, UC is modeled research, UC is modeled research, UC is modeled research, UC is modeled research, UC is modeled research, UC is modeled by adding the reliability and network adding the reliability and network adding the reliability and network adding the reliability and network adding the reliability and network adding the reliability and network adding the reliability and network adding the reliability and network adding the reliability and network adding the reliability and network adding the reliability and network adding the reliability and network adding the reliability and network adding the reliability and network adding the reliability and network adding the reliability and network adding the reliability and network adding the reliability and network co nstraints. nstraints. nstraints. Reliability constraint is incorporated into unit scheduling problem and Reliability constraint is incorporated into unit scheduling problem and Reliability constraint is incorporated into unit scheduling problem and Reliability constraint is incorporated into unit scheduling problem and Reliability constraint is incorporated into unit scheduling problem and Reliability constraint is incorporated into unit scheduling problem and Reliability constraint is incorporated into unit scheduling problem and Reliability constraint is incorporated into unit scheduling problem and Reliability constraint is incorporated into unit scheduling problem and Reliability constraint is incorporated into unit scheduling problem and Reliability constraint is incorporated into unit scheduling problem and Reliability constraint is incorporated into unit scheduling problem and Reliability constraint is incorporated into unit scheduling problem and Reliability constraint is incorporated into unit scheduling problem and Reliability constraint is incorporated into unit scheduling problem and Reliability constraint is incorporated into unit scheduling problem and Reliability constraint is incorporated into unit scheduling problem and Reliability constraint is incorporated into unit scheduling problem and Reliability constraint is incorporated into unit scheduling problem and Reliability constraint is incorporated into unit scheduling problem and Reliability constraint is incorporated into unit scheduling problem and Reliability constraint is incorporated into unit scheduling problem and Reliability constraint is incorporated into unit scheduling problem and Reliability constraint is incorporated into unit scheduling problem and Reliability constraint is incorporated into unit scheduling problem and Reliability constraint is incorporated into unit scheduling problem and Reliability constraint is incorporated into unit scheduling problem and Reliability constraint is incorporated into unit scheduling problem and Reliability constraint is incorporated into unit scheduling problem and Reliability constraint is incorporated into unit scheduling problem and Reliability constraint is incorporated into unit scheduling problem and Reliability constraint is incorporated into unit scheduling problem and it is solved it is solved it is solved it is solved by using genetic algorithm based on priority list (GABPL)by using genetic algorithm based on priority list (GABPL)by using genetic algorithm based on priority list (GABPL)by using genetic algorithm based on priority list (GABPL) by using genetic algorithm based on priority list (GABPL)by using genetic algorithm based on priority list (GABPL) by using genetic algorithm based on priority list (GABPL) by using genetic algorithm based on priority list (GABPL) by using genetic algorithm based on priority list (GABPL)by using genetic algorithm based on priority list (GABPL)by using genetic algorithm based on priority list (GABPL)by using genetic algorithm based on priority list (GABPL) by using genetic algorithm based on priority list (GABPL) by using genetic algorithm based on priority list (GABPL) by using genetic algorithm based on priority list (GABPL)by using genetic algorithm based on priority list (GABPL)by using genetic algorithm based on priority list (GABPL) by using genetic algorithm based on priority list (GABPL) by using genetic algorithm based on priority list (GABPL) by using genetic algorithm based on priority list (GABPL) by using genetic algorithm based on priority list (GABPL)by using genetic algorithm based on priority list (GABPL)by using genetic algorithm based on priority list (GABPL) by using genetic algorithm based on priority list (GABPL) by using genetic algorithm based on priority list (GABPL) by using genetic algorithm based on priority list (GABPL) by using genetic algorithm based on priority list (GABPL)by using genetic algorithm based on priority list (GABPL). Meanwhile, network constraints are incorporated into e Meanwhile, network constraints are incorporated into e Meanwhile, network constraints are incorporated into eMeanwhile, network constraints are incorporated into eMeanwhile, network constraints are incorporated into e Meanwhile, network constraints are incorporated into eMeanwhile, network constraints are incorporated into eMeanwhile, network constraints are incorporated into e Meanwhile, network constraints are incorporated into e Meanwhile, network constraints are incorporated into e Meanwhile, network constraints are incorporated into e Meanwhile, network constraints are incorporated into eMeanwhile, network constraints are incorporated into e Meanwhile, network constraints are incorporated into eMeanwhile, network constraints are incorporated into e Meanwhile, network constraints are incorporated into e Meanwhile, network constraints are incorporated into e Meanwhile, network constraints are incorporated into e Meanwhile, network constraints are incorporated into eMeanwhile, network constraints are incorporated into e Meanwhile, network constraints are incorporated into e Meanwhile, network constraints are incorporated into economic dispatchconomic dispatch conomic dispatchconomic dispatchconomic dispatch conomic dispatch (optimal optimal optimal power power flow) flow) and itand it and itand it is solved by by by using real coded genetic algorithm. using real coded genetic algorithm. using real coded genetic algorithm. using real coded genetic algorithm. using real coded genetic algorithm. using real coded genetic algorithm. using real coded genetic algorithm. using real coded genetic algorithm. using real coded genetic algorithm. using real coded genetic algorithm. using real coded genetic algorithm. using real coded genetic algorithm. using real coded genetic algorithm. using real coded genetic algorithm. using real coded genetic algorithm. using real coded genetic algorithm. Reliability Reliability Reliability Reliability Reliability Reliability Reliability Reliability constraint used in this research is lconstraint used in this research is l constraint used in this research is l constraint used in this research is l constraint used in this research is lconstraint used in this research is l constraint used in this research is l constraint used in this research is l constraint used in this research is l constraint used in this research is l constraint used in this research is l constraint used in this research is lconstraint used in this research is l constraint used in this research is lconstraint used in this research is lconstraint used in this research is l constraint used in this research is loss of load probability (LOLP) index oss of load probability (LOLP) index oss of load probability (LOLP) index oss of load probability (LOLP) index oss of load probability (LOLP) index oss of load probability (LOLP) index oss of load probability (LOLP) index oss of load probability (LOLP) index oss of load probability (LOLP) index oss of load probability (LOLP) index oss of load probability (LOLP) index oss of load probability (LOLP) index oss of load probability (LOLP) index oss of load probability (LOLP) index oss of load probability (LOLP) index oss of load probability (LOLP) index oss of load probability (LOLP) index oss of load probability (LOLP) index oss of load probability (LOLP) index oss of load probability (LOLP) index oss of load probability (LOLP) index which which is used to used to replace deterministic method for replace deterministic method for replace deterministic method for replace deterministic method for replace deterministic method for replace deterministic method for replace deterministic method for replace deterministic method for replace deterministic method for replace deterministic method for replace deterministic method for replace deterministic method for replace deterministic method for replace deterministic method for evaluatevaluat evaluat evaluatevaluating the adequacy of spinning the adequacy of spinning the adequacy of spinning the adequacy of spinning the adequacy of spinning the adequacy of spinning the adequacy of spinning the adequacy of spinning the adequacy of spinning the adequacy of spinning the adequacy of spinning the adequacy of spinning the adequacy of spinning the adequacy of spinning reserve in system reserve in system reserve in system reserve in systemreserve in systemreserve in system reserve in systemreserve in systemreserve in system . This research usin This research usinThis research usinThis research usin This research usinThis research usinThis research usinThis research usin This research usin g GABPL method is tested on 10 unit system g GABPL method is tested on 10 unit system g GABPL method is tested on 10 unit system g GABPL method is tested on 10 unit system g GABPL method is tested on 10 unit system g GABPL method is tested on 10 unit system g GABPL method is tested on 10 unit system g GABPL method is tested on 10 unit system g GABPL method is tested on 10 unit system g GABPL method is tested on 10 unit system g GABPL method is tested on 10 unit system g GABPL method is tested on 10 unit system g GABPL method is tested on 10 unit system g GABPL method is tested on 10 unit system g GABPL method is tested on 10 unit system g GABPL method is tested on 10 unit system g GABPL method is tested on 10 unit system g GABPL method is tested on 10 unit system g GABPL method is tested on 10 unit system g GABPL method is tested on 10 unit system with the duplication, 26 unit system, and IEEE RTS 24 bus system. with the duplication, 26 unit system, and IEEE RTS 24 bus system. with the duplication, 26 unit system, and IEEE RTS 24 bus system. with the duplication, 26 unit system, and IEEE RTS 24 bus system. with the duplication, 26 unit system, and IEEE RTS 24 bus system. with the duplication, 26 unit system, and IEEE RTS 24 bus system. with the duplication, 26 unit system, and IEEE RTS 24 bus system. with the duplication, 26 unit system, and IEEE RTS 24 bus system. with the duplication, 26 unit system, and IEEE RTS 24 bus system. with the duplication, 26 unit system, and IEEE RTS 24 bus system. with the duplication, 26 unit system, and IEEE RTS 24 bus system. with the duplication, 26 unit system, and IEEE RTS 24 bus system. with the duplication, 26 unit system, and IEEE RTS 24 bus system. with the duplication, 26 unit system, and IEEE RTS 24 bus system. with the duplication, 26 unit system, and IEEE RTS 24 bus system. with the duplication, 26 unit system, and IEEE RTS 24 bus system. with the duplication, 26 unit system, and IEEE RTS 24 bus system. with the duplication, 26 unit system, and IEEE RTS 24 bus system. with the duplication, 26 unit system, and IEEE RTS 24 bus system. with the duplication, 26 unit system, and IEEE RTS 24 bus system. with the duplication, 26 unit system, and IEEE RTS 24 bus system. Total operational costs Total operational costs Total operational costs Total operational costs Total operational costs Total operational costs Total operational costs Total operational costs Total operational costs Total operational costs obtained on 10 unit system with the duplication obtained on 10 unit system with the duplication obtained on 10 unit system with the duplication obtained on 10 unit system with the duplication obtained on 10 unit system with the duplication obtained on 10 unit system with the duplication obtained on 10 unit system with the duplication obtained on 10 unit system with the duplication obtained on 10 unit system with the duplication obtained on 10 unit system with the duplication obtained on 10 unit system with the duplication obtained on 10 unit system with the duplication obtained on 10 unit system with the duplication obtained on 10 unit system with the duplication obtained on 10 unit system with the duplication obtained on 10 unit system with the duplication obtained on 10 unit system with the duplication using GABPL method are using GABPL method areusing GABPL method are using GABPL method areusing GABPL method areusing GABPL method areusing GABPL method areusing GABPL method areusing GABPL method areusing GABPL method are using GABPL method areusing GABPL method are lower lowerlower compared with other methods.compared with other methods. compared with other methods.compared with other methods. compared with other methods. compared with other methods. compared with other methods. compared with other methods.compared with other methods. On 10 unit On 10 unit On 10 unit On 10 unit On 10 unit systesystesyste m, this method can obtained m, this method can obtained m, this method can obtained m, this method can obtained m, this method can obtained m, this method can obtained m, this method can obtained m, this method can obtained m, this method can obtained total cost of $563,937. total cost of $563,937.total cost of $563,937. total cost of $563,937.total cost of $563,937. total cost of $563,937. total cost of $563,937.total cost of $563,937. total cost of $563,937. On 26 unit system, this On 26 unit system, this On 26 unit system, this On 26 unit system, this On 26 unit system, this On 26 unit system, this On 26 unit system, this On 26 unit system, this On 26 unit system, this On 26 unit system, this On 26 unit system, this method can method can method can method can provide provide lower cost than compared method at LOLP 3% lower cost than compared method at LOLP 3%lower cost than compared method at LOLP 3% lower cost than compared method at LOLP 3%lower cost than compared method at LOLP 3% lower cost than compared method at LOLP 3% lower cost than compared method at LOLP 3%lower cost than compared method at LOLP 3% lower cost than compared method at LOLP 3%lower cost than compared method at LOLP 3%lower cost than compared method at LOLP 3%lower cost than compared method at LOLP 3% lower cost than compared method at LOLP 3%lower cost than compared method at LOLP 3% lower cost than compared method at LOLP 3%lower cost than compared method at LOLP 3%lower cost than compared method at LOLP 3%lower cost than compared method at LOLP 3%lower cost than compared method at LOLP 3%lower cost than compared method at LOLP 3% with the total with the total with the total with the total with the total with the total cost reduction of cost reduction of cost reduction of cost reduction of cost reduction of cost reduction of cost reduction of cost reduction of $5,718 or 0.76% $5,718 or 0.76%$5,718 or 0.76% $5,718 or 0.76%$5,718 or 0.76% . For the For the For the For the IEEE RTS 24 buIEEE RTS 24 bu IEEE RTS 24 bu IEEE RTS 24 buIEEE RTS 24 bu IEEE RTS 24 bu IEEE RTS 24 bu s system, this s system, this s system, this s system, this s system, this s system, this case case case case study study can can can be be solve d by usiby usiby usiby usi ng this proposed method with the increasing of total ng this proposed method with the increasing of total ng this proposed method with the increasing of total ng this proposed method with the increasing of total ng this proposed method with the increasing of total ng this proposed method with the increasing of total ng this proposed method with the increasing of total ng this proposed method with the increasing of total ng this proposed method with the increasing of total ng this proposed method with the increasing of total ng this proposed method with the increasing of total ng this proposed method with the increasing of total ng this proposed method with the increasing of total ng this proposed method with the increasing of total ng this proposed method with the increasing of total ng this proposed method with the increasing of total ng this proposed method with the increasing of total ng this proposed method with the increasing of total cost of cost of cost of cost of $24,167.48 or 3.247% compared with without considering $24,167.48 or 3.247% compared with without considering $24,167.48 or 3.247% compared with without considering$24,167.48 or 3.247% compared with without considering $24,167.48 or 3.247% compared with without considering$24,167.48 or 3.247% compared with without considering$24,167.48 or 3.247% compared with without considering $24,167.48 or 3.247% compared with without considering$24,167.48 or 3.247% compared with without considering $24,167.48 or 3.247% compared with without considering $24,167.48 or 3.247% compared with without considering $24,167.48 or 3.247% compared with without considering$24,167.48 or 3.247% compared with without considering$24,167.48 or 3.247% compared with without considering $24,167.48 or 3.247% compared with without considering $24,167.48 or 3.247% compared with without considering network network network constraints. constraints. constraints. constraints. constraints.